Conceptual Designs towards Developing Mechanically Controlled Semi-Automated Grass Cutter - Sivarao, Subramonian; T., Joseph Sahaya Anand; Hanizam, Hashim; Indra , Devi (IJENS Publishers, 2010)
Automatic control for grass cutting vehicle is required in order to cope with the environmental effect such as heat and rain, as well as strain on the driver. The driver of grass cutting vehicle or tractor has to operate or supervise the controlled and non-controlled implements along with vehicle guidance. Steering is a monotonous activity and tiring, which can result in reduced operation time and improve grass cutting quality. The need to overcome these setbacks was the motivation to develop a concept of a semi-automated steering guidance system for lawn tractors. This paper presents the design conceptualizations of a mechanism to semi-automate a grass cutting tractor. Several conceptual designs were generated and proposed for the mechanism to be equipped with the tractor for it to self-propel semi-automatically. The scope of the concepts is for the tractor to travel in a spiral pattern on a flat terrain at constant moving speed, and without external remote controlling devices. The characteristics and properties of the conceptual designs are discussed for their viability to be developed further into a prototype.